Resolva as equações a seguir a)7 (x - 2) = 5(x + 3) b) 7 (x - 1) - 2(x - 5) = x-5
Soluções para a tarefa
Respondido por
3
OI...
Resolva as equações a seguir:
a)
7(x - 2) = 5(x + 3)
7x - 14 = 5x + 15
7x - 5x = 15 + 14
2x = 29
x = 29/2
b)
7(x - 1) - 2(x - 5) = x - 5
7x - 7 - 2x + 10 = x - 5
5x + 3 = x - 5
5x - x = - 5 - 3
4x = - 8
x = - 8/4
x = - 2
Espero ter ajudado.
Perguntas interessantes
Matemática,
10 meses atrás
Biologia,
10 meses atrás
Português,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás